MENINGKATKAN KEMAMPUAN BERBICARA BAHASA INGGRIS MENGGUNAKAN APLIKASI PRACTICE ENGLISH SPEAKING TALK BAGI SISWA KELAS IX-A SMP NEGERI 15 TASIKMALAYA - Rahmat, Ade (Jurnal Inovasi dan Teknologi Pendidikan, 2023)
This research was conducted at SMP Negeri 15 Tasikmalaya in Class IX-A where the students' ability to speak English was quite low. The era of digitalization, which is called the era of the industrial revolution 4.0, made very fast changes. Many digital learning applications can be used effectively and efficiently as learning support media. This research requires innovative learning media so students don't feel bored during the teaching and learning process. There are many digital learning applications that can be used effectively and efficiently as learning support media. This classroom action research is entitled: "Improving English Speaking Skills Using the Practice English Speaking Talk Application for Class IX-A Students of SMP Negeri 15 Tasikmalaya". The purpose of writing this class action research is to find out whether the Conversation learning model can increase student activity and achievement. The data collection method is observation and learning achievement tests. The data analysis method is descriptive both for qualitative data and for quantitative data. The results obtained from this study are that Conversation can increase student activity and achievement. This is evident from the results obtained in Cycle I which was 6.3 for learning achievement. From Cycle I to Cycle II it rose to 7.9 for learning achievement. The conclusion obtained from this study is that the Conversation learning model can improve learning achievement